Molecular Identification and Physiological Characteristics of Trichoderma Isolates for the Biocontrol of Two Pathogens in Pineapple - Umaña Castro, Josué (2018)
Environmental pollution, associated with the excessive use of pesticides, has prompted the need for alternative practices in agriculture, such as the application of biological agents for controlling plant pathogens. Trichoderma is an agent that is amply used for biocontrol; however, the fungus is difficult to identify at the species level strictly by morphological examination. Additionally, the genus forms species complexes, which can make species identification much more challenging. Effective biocontrol products have to be easily reproducible in vitro, generate conidia with high germination rates, and demonstrate effective antagonistic activity against a target pathogen. The objective of this study was to determine if these desirable biocontrol traits are correlated with the genetic relationships of 15 Trichoderma isolates. We analyzed 15 monosporic Trichoderma isolates native to the northern region of Costa Rica; they had known antagonistic activity against pathogens associated with pineapple. We measured the growth rate and germination percentage. Mean growth rates varied from 0.90 to 1.20 mm · h-1 at 25 ºC. Germination percentage varied greatly from 3 % to 94 %. Species were identified by sequencing the translation elongation factor (TEF1-α) gene, and four species were identified: T. reesei, T. spirale, T. asperellum/asperelloides, and T. koningiopsis. Genetic distances within and among species were measured using six intermicrosatellites (ISSR). These distances showed high inter- and intraspecific diversity. Under a control lab environment, isolate 8a (T. reesei) showed the largest antagonistic effect against two pineapple pathogens, where there was a 30 % growth inhibition of Fusarium oxysporum and a 63 % growth inhibition of Pectobacterium carotovorum. A Mantel test showed that there was no correlation between genetic distances and Euclidean values for growth parameters and antagonistic response. We concluded that these traits were not species‑dependent; however, these isolates had high genetic diversity in a small, narrow geographical area with important biocontrol traits of interest.